2022
DOI: 10.31729/jnma.7364
|View full text |Cite
|
Sign up to set email alerts
|

Role of Tocilizumab in the Treatment of COVID-19 Patients with Cytokine Storm: A Case Series

Abstract: The in-hospital mortality in patients with COVID-19 could be correlated with severe acute respiratory syndrome coronavirus-2 induced hyper-inflammation, which is attributed to an unconstrained inflammatory cytokine storm. The pro-inflammatory cytokine, specifically, interleukin-6 plays a prominent role in the cytokine storm and may result in alveolar-capillary blood-gas exchange dysfunction. Therefore, the method to block the signal transduction pathway of interleukin-6 could be a potential treatment for sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…ACE2 mediates the infection of endothelial cells, leading to endothelial activation and damage [ 5 ]. Due to the abundant expression of ACE2, COVID-19 can induce tissue injury and immune dysregulation, resulting in highly elevated levels of inflammatory cytokines, such as IL-6 and CRP [ 6 ], as well as increased NLR [ 7 ]. Our study found that the CRP, IL-6, and NLR levels were significantly higher in the moderate-adult group compared to the mild-adult group, which can be attributed to the heightened activity of the inflammatory cytokine storm in moderate-adult cases.…”
Section: Discussionmentioning
confidence: 99%
“…ACE2 mediates the infection of endothelial cells, leading to endothelial activation and damage [ 5 ]. Due to the abundant expression of ACE2, COVID-19 can induce tissue injury and immune dysregulation, resulting in highly elevated levels of inflammatory cytokines, such as IL-6 and CRP [ 6 ], as well as increased NLR [ 7 ]. Our study found that the CRP, IL-6, and NLR levels were significantly higher in the moderate-adult group compared to the mild-adult group, which can be attributed to the heightened activity of the inflammatory cytokine storm in moderate-adult cases.…”
Section: Discussionmentioning
confidence: 99%